Self-Medication of Antibiotics among Medical and Nursing Students in a Medical College of Kathmandu - Sharma, Manoj; Khadka, Anjan; Kaundinnyayana, Sammodavardhana; Das, Premlata (Journal of Institute of Medicine Nepal, 2025)
Introduction The practice of self-medication of antibiotic among future healthcare professionals can lead to the emergence of antibiotic-resistant bacteria. This study aimed to investigate the prevalence, and underlying factors associated with self-medication of antibiotics among medical and nursing students. Methods A cross-sectional questionnaire based survey was conducted at Nepalese Army Institute of Health Sciences among second year students of MBBS and nursing streams after obtaining approval from Institutional Review Committee and informed consent from participants. The questionnaire comprised statements for knowledge, awareness and perception and practice. Descriptive parameters were used to summarize the data. Results The overall percentage of self-medication practice with different antibiotics was 31.41% within the past one year among 156 total participants. The two most common reasons for self-medication were convenience in getting antibiotics (MBBS 62.1%, BScN 25% and BNS 12.5%) and previous experiences of similar illness (MBBS 58.6%, BScN 66.7% and BNS 87.5%). Azithromycin was the most used antibiotic for self-medication by BNS (62.5%) and MBBS (58.6%) students whereas metronidazole was more commonly used by BScN students (41.7%). MBBS and BNS students primarily self medicated antibiotics for common cold and sorethroat, while BScN students commonly used them for fever and diarrhea. Conclusion This study revealed the practice of self-medication with antibiotics among medical and nursing students albeit less as compared to the other studies. However, such self-medication practice can adversely affect the future of antibiotic related issues especially emergence of antimicrobial resistance.